INFLUENCE OF THE ERGON TECHNIQUE ON THE PROPRIOCEPTION OF A PATIENT WITH A BIMALLEOLAR FRACTURE - Nasko Valchev; Mariya Gramatikova (Peytchinski Publishing, 2024)
Purpose: The aim of the study was to follow the influence of the Ergon Technique on proprioception in patients after surgical treatment of bimalleolar ankle fracture. Material/Methods: 30 patients with a bimalleolar fracture in the subacute postoperative period were studied, divided as follows: control group (CG) - 15 patients and experimental group (EG) - 15 patients. In CG, a traditional model of kinesitherapy is applied, and in EG, an experimental model is applied, which includes twice a week and Ergon Technique. To monitor changes in proprioception, a test was conducted: a balanced stance on the injured leg on a hard and flat surface was performed, and the time the patient maintained balance (in seconds) was recorded. Results: The mean values (±SD) after one month of kinesitherapy application are as follows: in the control group 0,9333+0,88 sec. and 3,0 sec. in the experimental group. After three months of treatment, the results are as follows: in the control group, 3,93+2,49 sec. And 9,2+4,19 sec. in the experimental group. The values of P show that the established difference in the mean values ​​of the indicator in the two groups after three months of kinesitherapy is statistically significant and proves a higher efficiency of the experimental model compared to the traditional one applied in the control group at P<0.05. Conclusion: In the conducted study, we found that there were statistically significant differences in both groups. In EG, we found that Ergon Tehnique has a better effect on proprioception in patients with bimalleolar fracture of the ankle joint compared to the applied traditional model of kinesitherapy in CG.